PENGEMBANGAN WEBSITE BUMIKITA.LIFE SEBAGAI MEDIA PSIKOEDUKASI PERILAKU PRO-LINGKUNGAN BAGI MASYARAKAT - Herdiyan Maulana; Santi Yudhistira; Gantina Komalasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract A growing trend of technology and information used in the last decade has transformed the way environmental activist delivering their massage into more an efficient method, the online platform. This current community service program focuses on psychoeducation attempt to enhance people’s awareness about the importance of pro-environmental behavior for the community. It was highly relevant using the online media as a method of delivering community relevant service activities to reach a wider community during the Covid-19 pandemic situation. Our effort to deliver this massage was carried out through the design and development of the website that contain information about the importance of environmentally friendly behavior. This psycho-educational website was designed and developed by involving community participation. The public can contribute to this website by submitting articles or any important information about environmental conservation. The website was designed in such a way as to attract people to access it. The domain of the website is bumikita.life, which describes the vision of our attempt which is drived by our concern towards environmental issues. While the domain